ВПЛИВ БІОПРЕПАРАТІВ НА ЕФЕКТИВНУ РОДЮЧІСТЬ ҐРУНТУ ТА МІНЕРАЛЬНЕ ЖИВЛЕННЯ САДЖАНЦІВ АЛИЧІ ТА АБРИКОСУ - Клименко, О. Є.; Клименко, М. І.; Камєнєва, І. О. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2015)
The effect of microbial preparations (MP) use, created on the basis of nitrogen-fixing and phosphorous mobilizing bacteria as well as complex of microbial preparations (CMP) on the effective soil fertility, mineral nutrition and efficiency of cherry plum and apricot seedlings growing was studied in the fruit nursery on the southern chernozems for three years. It was established that MP’s had a positive influence on the content of mineral elements in the soil and the leaves of fruit plants while promoting output of the standard planting material. Azotobacterine and CMP had the best effect on these indicators. Slight decrease of organic matter content in the soil under the cherry plum seedlings in MP variants was observed. Replenishment of the soil with organic matter is recommended for the effective use of MPs.